2013
DOI: 10.1038/bjc.2013.523
|View full text |Cite
|
Sign up to set email alerts
|

Mean overall survival gain with aflibercept plus FOLFIRI vs placebo plus FOLFIRI in patients with previously treated metastatic colorectal cancer

Abstract: Background:Mean survival in cancer trials can be estimated with statistical techniques to extrapolate study survival curves. This methodology was applied to data from the VELOUR trial, where use of the novel biologic aflibercept (ziv-aflibercept in the United States) in combination with fluorouracil+leucovorin+irinotecan (FOLFIRI), had significantly increased median overall survival (OS) by 1.44 months, vs placebo plus FOLFIRI in patients with metastatic colorectal cancer (mCRC) resistant to, or that had progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…[11] Finite mixture models allow for estimation of survival differences between treatment groups while differentiating the truly nonrecurrent cases from those women who did experience a recurrence but were misclassified because they did not receive SCS, chemotherapy or hospice care. Finite mixture models have been used to model cancer survival, [12,13] and have many applications in other areas of health services, biology, marketing, and engineering. [1417] This approach distinguishes between individuals with a greater probability to be in one group as compared to another, such as those with longer vs. shorter survival.…”
Section: Methodsmentioning
confidence: 99%
“…[11] Finite mixture models allow for estimation of survival differences between treatment groups while differentiating the truly nonrecurrent cases from those women who did experience a recurrence but were misclassified because they did not receive SCS, chemotherapy or hospice care. Finite mixture models have been used to model cancer survival, [12,13] and have many applications in other areas of health services, biology, marketing, and engineering. [1417] This approach distinguishes between individuals with a greater probability to be in one group as compared to another, such as those with longer vs. shorter survival.…”
Section: Methodsmentioning
confidence: 99%
“…The efficacy of intravenous aflibercept in combination with FOLFIRI in patients with mCRC who had progressed on or after completing treatment with an oxaliplatin-based regimen was evaluated in a pivotal, double-blind, multinational, phase 3 trial (VELOUR) [26], with these data supported by additional analyses [15,[30][31][32][33][34]. In addition, a global real-world Aflibercept Safety and Quality of life Program (ASQoP), which also included a French study (AFEQT), is evaluating aflibercept in a clinical setting similar to that of the VELOUR trial [35].…”
Section: Therapeutic Efficacy Of Afliberceptmentioning
confidence: 99%
“…Consistent with this finding, hazard ratios (HRs) for overall survival assessed at a 6-month intervals during the course of the VELOUR trial showed a continuous, consistent improvement with aflibercept plus FOLFIRI relative to placebo plus FOLFIRI (from 0.860 at B6 months to 0.676 at [18 months) [34]. Therefore, in order to assess the survival benefit beyond the end of the trial, mean overall survival was estimated by extrapolating survival curves from the VELOUR trial [31]. In the ITT population, with the best fit of statistical distribution (log-logistic), the estimated mean overall survival over 5 years was 19.5 months with aflibercept plus FOLFIRI and 16.5 months with placebo plus FOLFIRI (difference 3.0 months; 95 % CI 1.2-4.9) [31].…”
Section: Overall Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…A study was conducted to evaluate the mean OS gain with aflibercept plus FOLFIRI compared with placebo plus FOLFIRI in previously treated patients with mCRC [86]. The objective of the study was to analyze the implications of such survival estimations in the context of the VELOUR trial by generating mean OS differences between both study groups using parametric survival analyses.…”
Section: Aflibercept As Second-line Treatmentmentioning
confidence: 99%